2013
DOI: 10.1162/rest_a_00284
|View full text |Cite
|
Sign up to set email alerts
|

From Baghdad to London: Unraveling Urban Development in Europe, the Middle East, and North Africa, 800–1800

Abstract: This paper empirically investigates why, between 800 and 1800, the urban center of gravity moved from the Islamic world to Europe. Using a large new city-specific data set covering Europe, the Middle East, and North Africa, we unravel the role of geography and institutions in determining long-run city development in the two regions. We find that the main reasons for the Islamic world's stagnation and Europe's long-term success are specific to each region: any significant positive interaction between cities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
242
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(265 citation statements)
references
References 41 publications
10
242
1
1
Order By: Relevance
“…Physical geography: to capture the physical geography of each region we consider three key characteristics: its latitude, its access to the sea and its access to navigable rivers. These characteristics have been shown to be important for long-run economic development (Bosker & Buringh, 2017;Bosker, Buringh, & van Zanden, 2013;Gallup, Sachs, & Mellinger, 1999). .…”
Section: Explanatory Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical geography: to capture the physical geography of each region we consider three key characteristics: its latitude, its access to the sea and its access to navigable rivers. These characteristics have been shown to be important for long-run economic development (Bosker & Buringh, 2017;Bosker, Buringh, & van Zanden, 2013;Gallup, Sachs, & Mellinger, 1999). .…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…This is motivated by the fact that higher diversity is generally associated with lower levels of economic development (Alesina & Zhuravskaya, 2011;Beugelsdijk, Klasing & Milionis, 2017 the legacy of history on current TFP differences, we consider each region's historical urban density in 1800 based on data from Bairoch, Batou, and Chevre (1988). We also consider for each region how many cities were historically located on the crossing of two or more Roman roads, which Bosker et al (2013) have shown to be correlated with historical development over the past two millennia. Table 3 shows the descriptive statistics for all these explanatory variables, as well as their correlations with our baseline TFP estimate.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…5 We linearly interpolate (but never extrapolate) missing observations. To account for city-level features, we merge the Bairoch et al data with data from Bosker et al (2013), which leaves us with an unbalanced panel of 676 cities. 6 3 Thus, we use all available population data, including for cities with less than 5,000 inhabitants at some point in time.…”
Section: Datamentioning
confidence: 99%
“…The data base includes the city population for every fifty years between 1500 and 2000 AD. 41 We follow the recent update of the Bairoch et al (1988) population figures by Bosker et al (2013) and include the new, smaller figures for Bruges and Paris.…”
Section: Medieval Trade and City Developmentmentioning
confidence: 99%
“…Though regressions using this alternative measure are not shown in the main text due to space restrictions they are reported in Appendix C (Table C.2). 49 Finally, we estimate equations (6) and (7) using the data set of Bosker et al (2013), which contains city population figures for the years 800-1800 AD and a large set of variables representing important determinants of city development. Using this data offers the possibility to additionally control for urban potential, i.e.…”
mentioning
confidence: 99%